Prospective association between social engagement and cognitive impairment among middle-aged and older adults: evidence from the China Health and Retirement Longitudinal Study - Zhi-Jie Zheng; Yinzi Jin; Shuduo Zhou; Suhang Song (BMJ Open)
Objectives Cognitive impairment is a precursor of dementia. This study aimed to examine the association of social engagement with cognitive decline during the process of normal ageing.Methods We used data from the China Health and Retirement Longitudinal Study. The cognitive functions were tested at baseline, and 2-year and 4-year follow-up visits. Social engagement was constructed as a comprehensive measure including the quantity and frequency of social activities. Activities of social engagement were classified into three types. Multilevel logistic model was fitted to evaluate the prospective association between social engagement and cognitive impairment.Results After 2-year follow-up, compared with participants with the lowest level of social engagement, those with level-2, level-3 and level-4 social engagement had a 12% (OR=0.88, 95% CI 0.71 to 1.09, p=0.242), 17% (OR=0.83, 95% CI 0.71 to 0.97, p=0.020) and 25% (OR=0.75, 95% CI 0.61 to 0.93, p=0.008) lower risk for developing cognitive impairment, respectively. A similar pattern of significantly protective association was found at 4-year follow-up. Combined effect analysis showed that participants who attended one type of social engagement had a lower risk of developing cognitive impairment and the protective effect was even larger with those who attended two or three types of social engagement.Conclusions Social engagement had a protective effect on cognitive impairment among middle-aged and older adults in China. Given the growing epidemic of dementia and rapid pace of ageing in low-income and middle-income countries, our study shed lights on comprehensive and tailored public health programmes for improving social engagement, to delay cognitive impairment at mid-age and later life.